Numerical Modelling of Bird Strike on Aerospace Structures by means of Coupling FE-SPH - Abdullah, Nur Azam; Yusoff, Mohammad Daniel; Shahimi, Sharis - Shazzali; Meor Ahmad, Meor Iqram (International Journal of Integrated Engineering, 2021)
This article offers a parametric mechanics investigation in defining the correlation between the parameters of a wing-body during a bird strike collision. A commercial software of LS-Dyna is used to compute the numerical modelling manifested in this research. In this study, it is an attempt to form a definitive work based on the Smoothed Particle Hydrodynamics (SPH) formulation by recognising the most critical influencing parameters in the bird-strike computation and verify the simulation with the experiment data. For instance, an idealised bird is modelled as a cylindrical shape with hemispherical ends to maintain the homogeneity and symmetry using SPH approach. Moreover, an aluminium alloy rigid flat plate is modelled as a shell element plate in the finite element model (FEM). Here, internal energy vs time for different plate thickness graph are plotted to observe the difference of absorbed energy during the impact. Such conditions are considered in this research from the sight of bird strike impact under multiple states (structural thickness) and constraints (bird size). The obtained computational results are in adjacent agreement with the experimental results published in another literature.